2016
DOI: 10.1016/j.sjbs.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Urinary catheter indwelling clinical pathogen biofilm formation, exopolysaccharide characterization and their growth influencing parameters

Abstract: Self-reproducing microbial biofilm community mainly involved in the contamination of indwelling medical devices including catheters play a vital role in nosocomial infections. The catheter-associated urinary tract infection (CA-UTI) causative Staphylococcus aureus, Enterobacter faecalis, and Pseudomonas aeruginosa were selectively isolated, their phenotypic as well as genotypic biofilm formation, production and monomeric sugar composition of EPS as well as sugar, salt, pH and temperature influence on their in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 42 publications
1
28
1
Order By: Relevance
“…Were isolated. In contrast to our study, S.aureus (24%), P.aeruginosa (18%), E.faecalis (14%) and others (44%) were identified as etiological agents by Murugan [16]. In present study, the most resistant antibiotic were Ofloxacin followed by Co-Trimoxazole and isolates were mostly susceptible to Amikacin followed by Ceftizoxime antibiotics.…”
Section: Fig5 Frequency Wise Distribution Of Isolates F Antimicrobicontrasting
confidence: 92%
“…Were isolated. In contrast to our study, S.aureus (24%), P.aeruginosa (18%), E.faecalis (14%) and others (44%) were identified as etiological agents by Murugan [16]. In present study, the most resistant antibiotic were Ofloxacin followed by Co-Trimoxazole and isolates were mostly susceptible to Amikacin followed by Ceftizoxime antibiotics.…”
Section: Fig5 Frequency Wise Distribution Of Isolates F Antimicrobicontrasting
confidence: 92%
“…The inhibitory effect of E. gunnii EO against S. aureus confirmed the capability of the EOs recovered by species belonging to the Eucalyptus genus to block the biofilm formation by this methicillin resistant strain (Junka et al, 2019); its activity was more powerful than E. globulus EO (Merghni et al, 2018). The effectiveness shown by both EOs could be taken into consideration, once again, in patient management, mainly to avoid S. aureus infections that concern the central venous, dialysis (Gahlot et al, 2014), and urinary catheters (Murugan et al, 2016), as well as arteriovenous shunts (MacRae et al, 2016) and sutures (Henry-Stanley et al, 2010). Interestingly, L. petersonii EO at 0.5 µg/mL induced a strong inhibition of S. aureus biofilm formation (79.88%), while maintaining a high metabolic activity (90.89%) compared to the control.…”
Section: Biofilm and Metabolic Activity Of Biofilm Cellsmentioning
confidence: 55%
“…The high incidence of CAUTI at KRRH may be attributed to poor hygiene practices in relation to catheter handling, placement and maintenance. In addition previous studies have documented poor surveillance of hospital acquired infections, neglect of patient safety and health care quality as contributors to the high incidences of hospital acquired infections like CAUTI [19]. In a related study done in Zambia, a higher incidence of CAUTI (35%) was reported [6], however, the duration of catherisation was longer (28days) implying that the longer a catheter stays in-situ, the more likely it is to lead to an infection within the urinary tract as reported in other studies [10].…”
Section: Discussionmentioning
confidence: 99%